The Relationship Of Maternal Education And Family Support Towards Hypothyroid Screening At Rs. Ummi Bengkulu City In 2024 - Handayani, Ernawaty; Tepi R, Diyah; Sulastri, Mepi (Student Scientific Journal, 2025)
Congenital hypothyroidism is a general term for thyroid hormone deficiency due to thyroid gland dysfunction. Congenital Hypothyroidism Screening is a screening test to distinguish babies with Congenital Hypothyroidism from those without. The purpose of this study was to determine the relationship between mother's education and family support on hypothyroid screening at RS. UMMI in Bengkulu City in 2024. This study used a cross-sectional design. The population in this study was all newborns at RS. UMMI. The sample was taken using simple random sampling technique with a sample size of 76 babies. Data collection was obtained from questionnaires and the birth record register at RS. UMMI. The research results found that: (1) the majority of 40 mothers (52.6%) conducted hypothyroid screening; (2) the majority of 39 mothers (51.3%) had higher education; (3) the majority of 39 respondents (51.3%) did not receive family support; (4) there is a relationship between education with a ρ value = 0.002; (6) there is a relationship between family support with a ρ value = 0.006 and an OR value of 4. This study concluded that mother's education and family support greatly influence hypothyroid screening. It is hoped that after this study, more mothers will conduct hypothyroid screening on their babies, enabling early detection for optimal growth and development of the child in the future.